(3GdYhdeI Pdc GdNWQ GdbGOe (B:s (3CSHGHgG(B-(3JOGYjGJgG GdEbJUGOjI(B-(3BKGQgG GdJQHhjI (B/s - (3QLH, eUWais ((3YeGf(B: s (3eDSSI GdhQGb(B, s, 2008)
(3GdYhdeI hJOGYjGJgG GdGbJUGOjI,CgOGa hXGFa GdEYdGfGJ,GdBKGQ GdELJeGYjI hGdGbJUGOjI ddEYdGf,GdeOQSI hGdJQHjIs
(3HHdjhZQGajG(B:(3U U(B.189-198s
Keywords: (3GdEbJUGOs; (3GdJQHjIs; (3GdYhdeIs